Malaria and armed conflict (2020)
Background: to analyze the epidemiological behavior of Malaria in relation to armed conflicts presented on the Pacific coast of the Nariño (PCN). Methodology: it was a multi-group ecological study with secondary information source, it was analyzed the frequency of Malaria in the (PCN) population and the relationship with armed conflicts in the region resulting from the country’s internal conflict during 2003 to 2017. Results: Armed conflict affects the structure of health services which caring for the general population and malaria sufferers. The most common affections were the infrastructure, reduction in number of health personnel, conservation of vaccines and medicines, access to health care, the inability to do preventive activities and the poor presence of the government in the PCN area. Moreover, the displacement of the population to areas where the vector abounds increase the probability to get sick. Conclusions: This study found an inversely proportional relationship between the frequency of malaria cases and armed conflict. This situation could show that maybe the “conflict” controls malaria. However, it is important to clarify that could be only a masking the reality of the PCN, because the situation that was facing this region caused that the population could not access the Malaria’s programs and health services, making difficult the diagnose, treatment and notification to the public health surveillance systems. These aspects could contribute to a cases reduction during the armed conflict period.